(untitled) (Ius Novum, 2020)
China is one of the biggest states that are a source of cultural property in the world, which has been losing part of its priceless heritage since the middle of the 19th century due to plunder, illegal trade and intentional or accidental damage. Due to multi-century history and ethnic diversity, China adopted a hierarchical system of the protection of relics and a model of legislation based on co-existence of comprehensive and specialist legislation taking into account a special nature of some objects. The People’s Republic of China is a country with rich culture and long history which, thanks to the consistent improvement of legislation and integration with the international system of cultural property management, holds an important position in the global movement for the protection of relics. The article aims to present the most important issues concerning legal protection of cultural property in China.